Pain and glory [videorecording (DVD)] - Banderas, Antonio; Cruz, Penélope; Etxeandia, Asier, 1975-; Sbaraglia, Leonardo (Sony Pictures Home Entertainment, 2020)
It tells of a series of reencounters experienced by Salvador Mallo, a film director in his physical decline. Some of them in the flesh, others remembered: his childhood in the 60s, when he emigrated with his parents to a village in Valencia in search of prosperity, the first desire, his first adult love in the Madrid of the '80s, the pain of the breakup of that love while it was still alive and intense.